Analisis Stabilitas Lombong (Stope) Blok 1 SOD Level 7 Tambang Emas Bawah Tanah PT. Dempo Maju Cemerlang, Salido, Provinsi Sumatera Barat - Muhamad iqbal; Raimon Kopa (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. Research was conducted at the underground mine of PT Dempo Maju Cemerlang, which is focused in gold mining and is located in Pesisir Selatan Regency, West Sumatra Province. This research focuses on the analysis of the stability of the stope and pillar in mining. Mining activities are carried out with an underground mining system using the method, shrinkage stoping namely mining by creating a level level. Within these levels are made stopes or rooms. The blasted ore is removed as a whole, forming stope an empty. If it is feared that a collapse will occur, and this is undesirable, then the stope can be filled with waste originating from the tailing dump, therefore it is necessary to analyze the safety factor before and after filling the material using the help of software Phase2 with the mohr-coulumb collapse criteria. In detail, the observation area is carried out at Level 7 SOD Block 1 with block dimensions of 30 x 30 m. From the modeling results stope before and after the filling material, the safety factor is obtained from 1.59 to 3.63 so that it is categorized as safe. However, for the pillar safety factor, there is one point that is in critical condition, namely 1.03, so a support system recommendation is needed. For this reason, a simulation of giving is carried out shotcrete with a thickness of 100 mm on a critical pillar to increase the safety factor, so that the pillar safety factor is 1.63 so it is categorized as safe.Keywords: shrinkage stoping, safety factor, pillar, filling material